Aluminum hydroxide microsphere, preparation method and application in flame-retardant latex product

By preparing aluminum hydroxide microspheres, the problem of poor compatibility between aluminum hydroxide powder and latex sponge material is solved, and the good mechanical properties and flame retardant effect of latex sponge are achieved.

CN119823448APending Publication Date: 2025-04-15JIANGSU JSY LATEX PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510124114.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The poor compatibility of aluminum hydroxide powder and latex sponge materials leads to a significant reduction in the mechanical properties of latex sponge materials.

Method used

Aluminum hydroxide microspheres were used to prepare hydrophilic aluminum hydroxide microspheres by combining aluminum hydroxide with γ-cyclodextrin, potassium hydroxide solution, dispersant NNO, crosslinker EDTA and disodium hydrogen phosphate to improve their compatibility with latex sponge materials.

Benefits of technology

It effectively improves the compatibility of flame retardant and latex sponge material, maintains the mechanical properties of latex sponge, and achieves excellent flame retardant effects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an aluminum hydroxide microsphere, a preparation method and an application of the aluminum hydroxide microsphere in a latex product. The aluminum hydroxide microsphere comprises the following components in parts by weight: 80-100 parts of aluminum hydroxide; 20 to 50 parts of cyclodextrin; 20-50 parts of a potassium hydroxide solution; 5-10 parts of a dispersant NNO; 5 to 10 parts of a cross-linking agent EDTA; and 1 to 10 parts of disodium hydrogen phosphate. Aluminum hydroxide is wrapped by cyclodextrin to prepare aluminum hydroxide microspheres, and then the aluminum hydroxide microspheres are mixed with nano-zinc oxide for latex sponge foaming. The latex product prepared by the invention has flame retardant property and wide market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of latex products, and in particular to aluminum hydroxide microspheres, a preparation method and application in latex products. Background Art

[0002] With the continuous improvement of living standards, people are paying more and more attention to hygienic, safe and healthy products. With the progress of social economy and the continuous improvement of living standards, natural latex foam products are widely used in various fields, especially in the home furnishing field, which requires natural latex foam products to have good flame retardant properties. The burning of latex sponge will release a lot of heat and toxic smoke. The flame retardant and smoke suppression properties of latex sponge are directly related to fire safety, so the flame retardant and smoke suppression properties of natural latex products are widely concerned.

[0003] Aluminum hydroxide is a widely used green flame retardant and smoke suppressant with excellent properties such as low price, smoke suppression, environmental protection, odorless, and easy to combine with a variety of polymers. When aluminum hydroxide decomposes, it forms an oxide layer with high thermal stability and specific surface area, which can be used as a heat insulation layer to effectively prevent the transfer of heat and mass. In addition, aluminum hydroxide absorbs a large amount of heat when decomposed, and releases water vapor when decomposed, which can dilute the combustible gas on the surface of the material. Although the addition of aluminum hydroxide can improve the flame retardant and smoke suppression properties of latex sponge, its compatibility with latex sponge materials is poor, resulting in a significant reduction in the mechanical properties of latex sponge materials. Summary of the invention

[0004] To solve the above problems, the present invention provides aluminum hydroxide microspheres, a preparation method and application in latex products, which can effectively improve the compatibility of flame retardant and smoke suppressant with latex sponge materials, so that the mechanical properties of latex sponge can be maintained.

[0005] The technical solution of the present invention is: an aluminum hydroxide microsphere, comprising the following components in parts by weight: Aluminum hydroxide: 80-100 parts; Cyclodextrin: 20-50 parts; Potassium hydroxide solution: 20-50 parts; Dispersant NNO: 5-10 parts; Cross-linking agent EDTA: 5-10 parts; Disodium hydrogen phosphate: 1-10 parts.

[0006] The concentration of the potassium hydroxide solution is 2-6%.

[0007] The cyclodextrin is γ-cyclodextrin.

[0008] A method for preparing aluminum hydroxide microspheres comprises: firstly, dissolving cyclodextrin and aluminum hydroxide in a potassium hydroxide solution, adding a dispersant NNO, and performing ultrasonic vibration to make the solution uniform; Secondly, place the evenly dispersed mixed solution in a 55-65℃ water bath and stir; Then, add cross-linking agent EDTA and disodium hydrogen phosphate successively, stir at 85-95°C for 55-65 minutes, and then react at 155-165°C for 23-25 ​​hours; After the reaction is completed, the mixture is washed with distilled water and anhydrous ethanol in sequence; finally, the cyclodextrin polymer of aluminum hydroxide is obtained by drying and grinding.

[0009] The invention discloses an application of aluminum hydroxide microspheres in flame retardant latex products. The aluminum hydroxide microspheres are used for preparing flame retardant latex products.

[0010] The flame retardant latex product comprises the following components in parts by weight: Natural latex: 90-100 parts; Vulcanizing agent: 1-10 parts; Potassium oleate: 1-10 parts; Potassium ricinoleate: 0.5-5 parts; Potassium pyrophosphate: 0.1-5 parts; Hardener: 2-10 parts; Nano zinc oxide: 2-10 parts; Aluminum hydroxide microspheres: 4-20 parts.

[0011] The preparation method of the flame retardant latex product comprises: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 25-40℃ and the stirring is continued for 6-15h for pre-sulfurization treatment. The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added into a foaming device for foaming; (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0012] In step (1), the aluminum hydroxide microspheres and nano zinc oxide are mixed with a high-speed dispersing homogenizer for 5-20 minutes at a speed of 10000 r / min, and then pre-cured latex is added together with a hardener to inject air for foaming.

[0013] The particle size of the nano zinc oxide is less than 5 microns.

[0014] In the process of the present invention, flame retardant latex products are prepared by adding aluminum hydroxide microspheres. In order to avoid the influence of aluminum hydroxide powder on the latex structure, the present invention uses water-soluble γ-cyclodextrin to coat the flame retardant aluminum hydroxide, and the prepared aluminum hydroxide microspheres are added to the latex sponge to improve the compatibility of the flame retardant and the latex sponge material, while achieving the flame retardant effect and maintaining the mechanical properties. The present invention is green and environmentally friendly, and the prepared latex products have excellent flame retardant effects and mechanical properties, which are suitable for social needs. DETAILED DESCRIPTION

[0015] The present invention provides an aluminum hydroxide microsphere, comprising the following components in parts by weight: Aluminum hydroxide: 80-100 parts; Cyclodextrin: 20-50 parts; Potassium hydroxide solution: 20-50 parts; Dispersant NNO: 5-10 parts; Cross-linking agent EDTA: 5-10 parts; Disodium hydrogen phosphate: 1-10 parts.

[0016] In the traditional latex foaming process, aluminum hydroxide powder is added for flame retardancy and cost reduction. However, the addition of aluminum hydroxide powder to the latex foaming system will cause a decrease in mechanical and physical properties such as decreased tensile strength, decreased ball rebound, and increased permanent compression deformation.

[0017] The pH is kept alkaline by adjusting potassium hydroxide and disodium hydrogen phosphate, and cyclodextrin is relatively stable under alkaline conditions; aluminum hydroxide is evenly dispersed by dispersant NNO; aluminum hydroxide is allowed to enter the hydrophobic cavity of cyclodextrin by cross-linking agent EDTA, thereby obtaining hydrophilic aluminum hydroxide microspheres, which are convenient and reliable for latex product processing.

[0018] The concentration of the potassium hydroxide solution is 2-6%.

[0019] In this way, the pH is kept alkaline.

[0020] The cyclodextrin is γ-cyclodextrin.

[0021] The cavity of γ-cyclodextrin fits into the aluminum hydroxide.

[0022] A method for preparing aluminum hydroxide microspheres comprises: firstly, dissolving cyclodextrin and aluminum hydroxide in a potassium hydroxide solution, adding a dispersant NNO, and performing ultrasonic vibration to make the solution uniform; Secondly, place the evenly dispersed mixed solution in a 55-65℃ water bath and stir; Then, add cross-linking agent EDTA and disodium hydrogen phosphate successively, stir at 85-95°C for 55-65 minutes, and then react at 155-165°C for 23-25 ​​hours; After the reaction is completed, the mixture is washed with distilled water and anhydrous ethanol in sequence; finally, the cyclodextrin polymer of aluminum hydroxide is obtained by drying and grinding.

[0023] In this way, cyclodextrin-coated aluminum hydroxide is prepared, which has hydrophilicity and is better soluble in a natural latex mixed system in an aqueous system.

[0024] The invention discloses an application of aluminum hydroxide microspheres in flame retardant latex products. The aluminum hydroxide microspheres are used for preparing flame retardant latex products.

[0025] The flame retardant latex product comprises the following components in parts by weight: Natural latex: 90-100 parts; Vulcanizing agent: 1-10 parts; Potassium oleate: 1-10 parts; Potassium ricinoleate: 0.5-5 parts; Potassium pyrophosphate: 0.1-5 parts; Hardener: 2-10 parts; Nano zinc oxide: 2-10 parts; Aluminum hydroxide microspheres: 4-20 parts.

[0026] In application, the vulcanizing agent is such as sulfur dispersion and the hardening agent is such as sodium fluorosilicate dispersion.

[0027] Hydrophilic aluminum hydroxide microspheres are added to the Dunlop sponge foaming formula to improve flame retardancy.

[0028] The preparation method of the flame retardant latex product comprises: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 25-40℃ and the stirring is continued for 6-15h for pre-sulfurization treatment. The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added into a foaming device for foaming; (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0029] In step (1), the aluminum hydroxide microspheres and nano zinc oxide are mixed with a high-speed dispersing homogenizer for 5-20 minutes at a speed of 10000 r / min, and then pre-cured latex is added together with a hardener to inject air for foaming.

[0030] It is added during the foaming process to further prevent the aluminum hydroxide microspheres from agglomerating and to make them evenly dispersed in the alkaline latex foaming system.

[0031] The particle size of the nano zinc oxide is less than 5 microns.

[0032] When the zinc oxide particle size is less than 5 microns, it has a larger surface area and better thermal stability. Because during the use of latex foam products, hydrogen sulfide generated by the breakage of polysulfide bonds will accelerate the cracking of rubber, zinc oxide and hydrogen sulfide groups will react to generate new cross-linking bonds, and the broken rubber macromolecules will re-bond. Zinc oxide can accelerate the vulcanization process of rubber, allowing the rubber molecular chain to complete cross-linking at a lower temperature and in a shorter time, making the latex foam products have better thermal stability, thereby improving flame retardancy.

[0033] The following are some examples: Examples of aluminum hydroxide microspheres are as follows: Example 1 is: an aluminum hydroxide microsphere includes the following components in parts by weight: aluminum hydroxide: 80 parts; cyclodextrin: 20 parts; potassium hydroxide solution: 20 parts; dispersant NNO: 5 parts; cross-linking agent EDTA: 5 parts; disodium hydrogen phosphate: 2 parts.

[0034] Example 2 is: an aluminum hydroxide microsphere includes the following components in parts by weight: aluminum hydroxide: 90 parts; cyclodextrin: 30 parts; potassium hydroxide solution: 30 parts; dispersant NNO: 8 parts; cross-linking agent EDTA: 8 parts; disodium hydrogen phosphate: 5 parts.

[0035] Example 3 is: an aluminum hydroxide microsphere includes the following components in parts by weight: aluminum hydroxide: 100 parts; cyclodextrin: 50 parts; potassium hydroxide solution: 50 parts; dispersant NNO: 10 parts; cross-linking agent EDTA: 10 parts; disodium hydrogen phosphate: 10 parts.

[0036] The present invention provides three ratios of aluminum hydroxide microspheres with better performance.

[0037] Examples of flame retardant latex products are as follows: Example 1 The preparation process of flame retardant latex products includes the following steps: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 25° C. and the stirring is continued for 6-15 hours, and the pre-sulfurization treatment is performed. The raw materials include the following components in parts by weight: Natural latex: 100 parts; Vulcanizing agent: 7 parts; Potassium oleate: 3 parts; Potassium ricinoleate: 1 part; Potassium pyrophosphate: 0.1 part; The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added to a foaming device in a certain proportion for foaming. The hardener is 4 parts, the nano zinc oxide is 6 parts, and the aluminum hydroxide microspheres are 4 parts.

[0038] (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0039] The specific preparation steps of the aluminum hydroxide microspheres are as follows: dissolving γ-cyclodextrin and aluminum hydroxide in a 2% potassium hydroxide solution, adding dispersant NNO, and evenly oscillating by ultrasonication, then placing the evenly dispersed mixed solution in a 55°C water bath and stirring, using EDTA as a crosslinking agent, and adding disodium hydrogen phosphate as a catalyst, stirring at 85°C for 55 minutes, and then reacting at 155°C for 23 hours. After the reaction is completed, washing with distilled water and anhydrous ethanol in turn, and finally drying and grinding to obtain the cyclodextrin polymer of aluminum hydroxide, i.e., aluminum hydroxide microspheres.

[0040] Example 2 The preparation process of flame retardant latex products includes the following steps: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 30° C. and the stirring is continued for 6-15 hours, and the pre-sulfurization treatment is performed. The raw materials include the following components in parts by weight: Natural latex: 100 parts; Vulcanizing agent: 6 parts; Potassium oleate: 3 parts; Potassium ricinoleate: 2 parts; Potassium pyrophosphate: 0.5 parts; The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added to a foaming device in a certain proportion for foaming. The hardener is 4 parts, the nano zinc oxide is 6 parts, and the aluminum hydroxide microspheres are 8 parts.

[0041] (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0042] The specific preparation steps of the aluminum hydroxide microspheres are as follows: dissolving γ-cyclodextrin and aluminum hydroxide in a 3% potassium hydroxide solution, adding dispersant NNO, and evenly oscillating by ultrasonication, then placing the evenly dispersed mixed solution in a 60°C water bath and stirring, using EDTA as a crosslinking agent, and adding disodium hydrogen phosphate as a catalyst, stirring at 90°C for 60 minutes, and then reacting at 160°C for 24 hours. After the reaction is completed, washing with distilled water and anhydrous ethanol in turn, and finally drying and grinding to obtain the cyclodextrin polymer of aluminum hydroxide, i.e., aluminum hydroxide microspheres.

[0043] Example 3 The preparation process of flame retardant latex products includes the following steps: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 35° C. and the stirring is continued for 6-15 hours, and the pre-sulfurization treatment is performed. The raw materials include the following components in parts by weight: Natural latex: 100 parts; Vulcanizing agent: 10 parts; Potassium oleate: 4 parts; Potassium ricinoleate: 3 parts; Potassium pyrophosphate: 3 parts; The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added to a foaming device in a certain proportion for foaming. The hardener is 4 parts, the nano zinc oxide is 6 parts, and the aluminum hydroxide microspheres are 12 parts.

[0044] (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0045] The specific preparation steps of the aluminum hydroxide microspheres are as follows: dissolving γ-cyclodextrin and aluminum hydroxide in a 4% potassium hydroxide solution, adding dispersant NNO, and evenly oscillating by ultrasonication, then placing the evenly dispersed mixed solution in a 60°C water bath and stirring, using EDTA as a crosslinking agent, and adding disodium hydrogen phosphate as a catalyst, stirring at 85°C for 65 minutes, and then reacting at 160°C for 25 hours. After the reaction is completed, washing with distilled water and anhydrous ethanol in turn, and finally drying and grinding to obtain the cyclodextrin polymer of aluminum hydroxide, i.e., aluminum hydroxide microspheres.

[0046] Example 4 The preparation process of flame retardant latex products includes the following steps: (1) Raw material preparation and pre-vulcanization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 40° C. and the stirring is continued for 6-15 hours, and the pre-vulcanization treatment is performed. The raw materials include the following components in parts by weight: Natural latex: 90 parts; Vulcanizing agent: 4 parts; Potassium oleate: 5 parts; Potassium ricinoleate: 5 parts; Potassium pyrophosphate: 2 parts; The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added to a foaming device in a certain proportion for foaming. The hardener is 4 parts, the nano zinc oxide is 6 parts, and the aluminum hydroxide microspheres are 16 parts.

[0047] (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0048] The specific preparation steps of the aluminum hydroxide microspheres are as follows: dissolving γ-cyclodextrin and aluminum hydroxide in a 5% potassium hydroxide solution, adding dispersant NNO, and evenly oscillating by ultrasonication, then placing the evenly dispersed mixed solution in a 62°C water bath and stirring, using EDTA as a crosslinking agent, and adding disodium hydrogen phosphate as a catalyst, stirring at 92°C for 60 minutes, and then reacting at 162°C for 24.5 hours. After the reaction is completed, washing with distilled water and anhydrous ethanol in turn, and finally drying and grinding to obtain the cyclodextrin polymer of aluminum hydroxide, i.e., aluminum hydroxide microspheres.

[0049] Example 5 The preparation process of flame retardant latex products includes the following steps: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 30° C. and the stirring is continued for 6-15 hours, and the pre-sulfurization treatment is performed. The raw materials include the following components in parts by weight: Natural latex: 100 parts; Vulcanizing agent: 6 parts; Potassium oleate: 5 parts; Potassium ricinoleate: 3 parts; Potassium pyrophosphate: 2 parts; The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added to a foaming device in a certain proportion for foaming. The hardener is 4 parts, the nano zinc oxide is 6 parts, and the aluminum hydroxide microspheres are 20 parts.

[0050] (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

[0051] The specific preparation steps of the aluminum hydroxide microspheres are as follows: dissolving γ-cyclodextrin and aluminum hydroxide in a 5% potassium hydroxide solution, adding dispersant NNO, and evenly oscillating by ultrasonication, then placing the evenly dispersed mixed solution in a 65°C water bath and stirring, using EDTA as a crosslinking agent, and adding disodium hydrogen phosphate as a catalyst, stirring at 95°C for 65 minutes, and then reacting at 165°C for 25 hours. After the reaction is completed, washing with distilled water and anhydrous ethanol in turn, and finally drying and grinding to obtain the cyclodextrin polymer of aluminum hydroxide, i.e., aluminum hydroxide microspheres.

[0052] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Aluminum hydroxide microspheres 4 8 12 16 20 <![CDATA[Density / kg / m 3 > 85.0 85.1 85.0 84.8 84.9 Tensile strength / kPa 78.5 80.4 80.2 79.5 80.5 Permanent compression set ≤10 ≤10 ≤10 ≤10 ≤10 Ball Rebound 65% 65% 64% 63% 63% Flame retardant grade B3 B2 B2 B1 B1 Note: B1 is flame retardant, B2 is flammable, and B3 is flammable.

[0053] Under the same density conditions, by comparing the mechanical and physical properties (tensile strength, permanent compression deformation, ball rebound) and flame retardant grade of the sponge, it can be seen that with the increase in the proportion of aluminum hydroxide microspheres, the flame retardant grade of the latex sponge also increases accordingly. At the same time, it has good mechanical and physical properties.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.

Claims

1. Aluminum hydroxide microspheres, characterized in that The composition comprises the following components in parts by weight: Aluminum hydroxide: 80-100 parts; Cyclodextrin: 20-50 parts; Potassium hydroxide solution: 20-50 parts; Dispersant NNO: 5-10 parts; Cross-linking agent EDTA: 5-10 parts; Disodium hydrogen phosphate: 1-10 parts.

2. A kind of aluminum hydroxide microsphere according to claim 1, characterized in that, The concentration of the potassium hydroxide solution is 2-6%.

3. A kind of aluminum hydroxide microsphere according to claim 1, characterized in that, The cyclodextrin is γ-cyclodextrin.

4. A method for preparing aluminum hydroxide microspheres according to any one of claims 1 to 3, characterized in that: include: First, cyclodextrin and aluminum hydroxide were dissolved in potassium hydroxide solution, and dispersant NNO was added and ultrasonically vibrated to make them uniform. Secondly, place the evenly dispersed mixed solution in a 55-65℃ water bath and stir; Then, add cross-linking agent EDTA and disodium hydrogen phosphate successively, stir at 85-95°C for 55-65 minutes, and then react at 155-165°C for 23-25 ​​hours; After the reaction is completed, the mixture is washed with distilled water and anhydrous ethanol in sequence; finally, the cyclodextrin polymer of aluminum hydroxide is obtained by drying and grinding.

5. Use of the aluminum hydroxide microspheres according to any one of claims 1 to 3 in flame retardant latex products, characterized in that: Aluminum hydroxide microspheres are used in the preparation of flame retardant latex products.

6. The use of aluminum hydroxide microspheres in flame retardant latex products according to claim 5, characterized in that: The flame retardant latex product comprises the following components in parts by weight: Natural latex: 90-100 parts; Vulcanizing agent: 1-10 parts; Potassium oleate: 1-10 parts; Potassium ricinoleate: 0.5-5 parts; Potassium pyrophosphate: 0.1-5 parts; Hardener: 2-10 parts; Nano zinc oxide: 2-10 parts; Aluminum hydroxide microspheres: 4-20 parts.

7. The use of aluminum hydroxide microspheres in flame retardant latex products according to claim 6, characterized in that: The preparation method of the flame retardant latex product comprises: (1) Raw material preparation and pre-sulfurization: After the raw materials are prepared according to the formula and stirred evenly, the temperature is 25-40℃ and the stirring is continued for 6-15h for pre-sulfurization treatment. The pre-cured latex, hardener, nano zinc oxide and aluminum hydroxide microspheres prepared above are added into a foaming device for foaming; (2) Vulcanization process: high temperature steam vulcanization treatment to gel and fix the shape; (3) Drying of finished product.

8. The use of aluminum hydroxide microspheres in latex products according to claim 7, characterized in that: In step (1), the aluminum hydroxide microspheres and nano zinc oxide are mixed with a high-speed dispersing homogenizer for 5-20 minutes at a speed of 10000 r / min, and then pre-cured latex is added together with a hardener to inject air for foaming.

9. The use of aluminum hydroxide microspheres in flame retardant latex products according to claim 6, characterized in that: The particle size of the nano zinc oxide is less than 5 microns.